(untitled) (Bangkok, 2005)
List of content: genetic resources and breeding; Biotechnology; Cultural practices and physiology: nutrient, nitrogent, carbohyrate, NPK...; Plant protection.
Keywords: Tropical fruit,Longan,Lychee,Rambutan